COVID-19 IN INDONESIA: ANALYSIS OF DIFFERENCES EARNINGS MANAGEMENT IN THE FIRST QUARTER - Widyaningsih Azizah (UNIB Press, 2021)
The COVID-19 pandemic, which began in the first quarter (Q1) of 2020 in Indonesia, has certainly had a major impact on the company’s financial performance. The first-quarter financial report should have been able to show the actual condition of the financial company because it can be a projection for investors and analysts regarding the company’s performance in the next period. Unfortunately, many gaps in financial reporting that can provide space for management to commit earnings management. This study aims to prove the difference in earnings management in the Q1 of 2020, namely the period after the COVID-19 pandemic with the Q1 of 2019, namely the period before the COVID-19 pandemic. The data type of the research is secondary data using the financial statements of companies listed on the Indonesian Stock exchange in the Q1 of 2018, the Q1 of 2019, and the Q1 of 2020. The Q1 of 2018 is needed in this research related to the search for the Q1 of the year of 2019 data. Hypothesis testing was conducted using the Wilcoxon test with SPSS 25 software. This research has proven that there is a difference in earnings management in the Q1 of 2019, namely before the COVID-19 pandemic, and the Q1 of 2020, named after the COVID-19 pandemic. The level of earnings management during the COVID-19 pandemic represented in the Q1 of 2020 was lower than the earnings management in the period before the COVID-19 pandemic, namely in the Q1 of 2019.